Effectiveness of Muscle Energy Technique and Proprioceptive Neuromuscular Facilitation in Knee Osteoarthritis: Life Sciences-Physiotherapy for better pain management - Minal Bharat Masekar; Dr. Amrutkuvar Rayjade; Dr.Trupti Yadav; Dr.Khushboo Chotai (International Journal of Life Science and Pharma Research, 2022)
This study was undertaken to determine the effectiveness of techniques such as muscle energy technique and proprioceptive neuromuscular facilitation in reduction of pain levels, improvement in flexibility of hamstring muscle and functional mobility, in patients with osteoarthritis of knee. An experimental study was carried out using a pre test and post test study design. The study was carried out in Krishna Hospital, Karad with a sample size of 36 individuals suffering from osteoarthritis of knee using a random sampling method. Individuals with Osteoarthritis of knee within the age group 40-60 years have been included. The collected data was analysed using paired and unpaired ‘t’ tests. When the data was analysed, the results showed that the patients in Group A and B receiving PNF stretching and MET respectively, the pain levels measured using NPRS shows more improvement in group A(7.66 ±1.02 ) as compared to group B (3.44 ±0.92). Hamstring flexibility in group A (10.63 ±4.89) was also found to be higher than in group B (4.37±2.01) when Active knee extension test was performed as a measure for hamstring flexibility, when functional mobility was measured using Western Ontario and McMaster universities arthritis index, improvement seen in group A (27.21 ±12.31) was significantly higher than in group B (14.11±7.88). The primary finding was that the patients of group A receiving PNF stretching along with the baseline protocol showed better improvement in pain levels, hamstring flexibility and level of functional mobility as compared to the patients in group B receiving MET along. with baseline protocol